ПРИРОДНА КОНВЕКЦІЯ РЕАЛЬНОГО ГАЗУ БІЛЯ ВЕРТИКАЛЬНОЇ НАГРІТОЇ СТІНКИ - Avramenko, A.A.; Kovetska, M.M.; Dmitrenko, N.P.; Kovetska, Yu.Yu. (Institute of Engineering Thermophysics of NAS of Ukraine, 2022)
The development of industry constantly requires reliable and long-lasting operation of various equipment with gas working bodies. In this regard, the accumulation of information related to the physicochemical, thermophysical, hydrodynamic properties of gases is constantly relevant. If the technological problems are occur at high pressures and phase transitions, the laws of ideal gases do not apply in such cases, because the parameters of the gas undergo significant changes. Therefore, the aim of this paper is to analyze the influence of thermophysical properties of Van der Waals gas on heat transfer of natural convection near a vertical heated wall, and to compare the influence of the equation of state of ideal and real gases on the characteristics of natural convection. Symmetry analysis is used to solve this problem. The influence of the van der Waals equation of state on the characteristics of convective heat transfer is studied, and the obtained results are compared with the case of an ideal gas. It is shown that increasing the parameter a  in the equation of state of the flow increases the velocity in the near-wall layer compared to the ideal gas, and increasing the parameter b  leads to a slowdown in flow. The intensification and deterioration of heat transfer in the natural convection of real gas are also due to the effects of nonlinearity in the van der Waals equation and are related with the influence of Van der Waals parameters on the velocity profile.